Australia's oldest marsupial fossils and their biogeographical implications. - Robin M D Beck (Public Library of Science (PLoS), 2008)
Background We describe new cranial and post-cranial marsupial fossils from the early Eocene Tingamarra Local Fauna in Australia and refer them to Djarthia murgonensis, which was previously known only from fragmentary dental remains. Methodology/principal findings The new material indicates that Djarthia is a member of Australidelphia, a pan-Gondwanan clade comprising all extant Australian marsupials together with the South American microbiotheres. Djarthia is therefore the oldest known crown-group marsupial anywhere in the world that is represented by dental, cranial and post-cranial remains, and the oldest known Australian marsupial by 30 million years. It is also the most plesiomorphic known australidelphian, and phylogenetic analyses place it outside all other Australian marsupials. Conclusions/significance As the most plesiomorphic and oldest unequivocal australidelphian, Djarthia may approximate the ancestral morphotype of the Australian marsupial radiation and suggests that the South American microbiotheres may be the result of back-dispersal from eastern Gondwana, which is the reverse of prevailing hypotheses.